Intrahepatic portal vein blood volume estimated by non-contrast magnetic resonance imaging for the assessment of portal hypertension - Uribe, S. (2015)
Purpose: To investigate the feasibility of estimating the portal vein blood volume that flows into the intrahepatic volume (IHPVBV) in each cardiac cycle using non-contrast MR venography technique as a surrogate marker of portal hypertension (PH). Materials and methods: Ten patients with chronic liver disease and clinical symptoms of PH (40% males, median age: 54.0, range: 44-73 years old) and ten healthy volunteers (80% males, median age: 54.0, range: 44-66 years old) were included in this study. A non-contrast Triple-Inversion-Recovery Arterial-Spin-Labeling (TIR-ASL) technique was used to quantify the IHPVBV in one and two cardiac cycles. Liver (LV) and spleen volumes (SV) were measured by manual segmentation from anatomical MR images as morphological markers of PH. All images were acquired in a 1.5. T Philips Achieva MR scanner. Results: PH patients had larger SV (P=0.02) and lower liver-to-spleen ratio (P=0.02) compared with healthy volunteers. The median IHPVBV in healthy volunteers was 13.5cm3 and 26.5cm3 for one and two cardiac cycles respectively, whereas in PH patients a median volume of 3.1cm3 and 9.0cm3 was observed. When correcting by LV, the IHPVBV was significantly higher in healthy volunteers than PH patients for one and two cardiac cycles. The combination of morphological information (liver-to-spleen ratio) and functional information (IHPVBV/LV) can accurately identify the PH patients with a sensitivity of 90% and specificity of 100%. Conclusion: Results show that the portal vein blood volume that flows into the intrahepatic volume in one and two cardiac cycles is significantly lower in PH patients than in healthy volunteers and can be quantified with non-contrast MRI techniques. © 2015.